Physical self-concept and its link to cardiopulmonary exercise tolerance among adolescents with mild congenital heart disease. (1st June 2015) - Chen, Chi-Wen; Su, Wen-Jen; Wang, Jou-Kou; Yang, Hsiao-Ling; Chiang, Yueh-Tao; Moons, Philip
Abstract: Background: Due to medical advances, most children with congenital heart disease (CHD) are expected to survive into adulthood. Establishing adequate physical self-concept and cardiopulmonary tolerance during the adolescent period can primarily enhance overall well-being. Aim: The purpose of this study was to undertake a gender-specific evaluation of the domain of physical self-concept among adolescents with mild CHD, and to examine the relationships between physical self-concept and cardiopulmonary exercise tolerance among adolescents with mild CHD. Methods: Four hundred and thirteen adolescents 12–20 years of age, whose cardiologists had not recommended any limitation of exercise, completed Physical Self-Description Questionnaires and three-minute step tests in two outpatient cardiology departments. Results: The male participants had significantly greater scores in measures of overall physical self-concept, competence in sports, physical appearance, body fat, physical activity, endurance, and strength than did the female participants. More than 80% of the participants had at least an average cardiopulmonary exercise tolerance index. The perception of not being 'too fat' and being more physically active were significant correlates of better cardiopulmonary exercise tolerance for adolescents with mild CHD. Conclusions: The results provided evidence for gender-specific evaluation of domains of physical self-concept among adolescents with mild CHD. The three-minute step test to measure cardiopulmonary exercise tolerance in adolescents with mild CHD may be an appropriate objective measure for use in future research. Continued efforts are needed in early intervention to promote cardiopulmonary exercise tolerance.